Peningkatan Hasil Belajar IPAS Melalui Model Problem Based Learning Terintegrasi Teaching at the Right Level Siswa Kelas VI Sekolah Dasar - Umami, Retno Rhisalatul; Utaminingsih, Sri (STKIP HARAPAN BIMA, 2025)
The problem in the study difficulty of teachers in determining effective science learning strategies which resulted in low learning outcomes. The study aimed improve science learning outcomes through the application of integrated Problem Based Learning model TaRL for grade VI students of SD 1 Bakalan Krapyak. This study a Classroom Action Research (CAR) carried out in 2 cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects of the study were 20 grade VI students. The data collection techniques used observation, interviews, and learning outcome tests. The data analysis technique used descriptive quantitative. The results of study showed increase in learning outcomes each cycle. Classically, learning outcomes in cycle I obtained average 72.8 and cycle II with average 78.5. The percentage of learning outcomes completed cycle I 55% and cycle II 70%. The results of study concluded was successful in improving learning outcomes because had achieved the established success indicators, namely student learning outcomes reaching an average of ? 75. The school should provide support and encourage teachers, especially in science subjects, to create active and innovative learning processes. Thus, students will be more enthusiastic and motivated so that it will have an impact on improving learning outcomes.